DIALOGISM: PHILOSOPHY OF HUMAN EXISTENCE AND CULTURAL PRODUCTION IN THE NOVEL “THEIR EYES WATCHING GOD” (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the concept of dialogism in Zora Neale Hurston’s Their Eyes Were Watching God, examining how the novel embodies Mikhail Bakhtin’s theory of dialogue as a fundamental principle of human existence and cultural production. Hurston’s work is deeply rooted in the interplay of multiple voices, perspectives, and linguistic styles, reflecting the dynamic and evolving nature of identity, social interaction, and cultural expression. Through Janie’s journey of self-discovery, the novel illustrates how meaning is constructed through dialogue—both literal and metaphorical—between individuals, communities, and historical narratives. By analyzing the novel’s use of African American Vernacular English (AAVE), narrative shifts, and polyphonic storytelling, this study argues that Their Eyes Were Watching God serves as a literary manifestation of dialogism, challenging monologic structures and asserting the richness of Black cultural discourse. The findings suggest that Hurston’s novel not only portrays the complexity of human relationships but also situates language as a site of resistance, identity formation, and cultural continuity.